The Distribution of Social Capital across Individuals and its Relationship to Income - Kevin Corinth; Thomas O'Rourke; Scott Winship (Institute of Labor Economics (IZA), 2024)
There have been several attempts to measure social capital—the value inhering in relationships—at an aggregate level, but researchers lack comprehensive individual-level social capital measures. Using a combination of direct linkage and imputation across several nationally representative datasets, we produce a comprehensive measure of social capital at the individual level. We validate our measure by aggregating it to the state level, finding strong correlations with existing state-level social capital measures. We document substantial social capital disparities between white Americans, on the one hand, and black and Hispanic Americans, on the other, as well as a strong educational gradient, which is comparatively weaker for Hispanics. We also provide new evidence on the relationship between income and social capital, using a comprehensive measure of income. We find that social capital increases with income but at a decreasing rate. The source of income matters, as an extra 10,000 in market income is associated with a 0.23 standard deviation increase in social capital for those with the lowest levels of market income, while an extra 10,000 in government transfer income is associated with a 0.08 standard deviation decrease.
Keywords: Z13; J12; D31; 330; social capital; comprehensive income; inequality